Emission of microplastics particles during the mechanical removal of polymer materials in cosmetics industry - Drewniak, Sabina; Wika, Ewa; Drewniak, Łukasz (Photonics Letters of Poland, 2025)
Plastics and microplastics represent an increasing threat to both the environment and human health, particularly in enclosed spaces such as beauty salons. This study presents a preliminary characterization of microplastic particles generated during the milling of various nail styling materials. Morphological analyses were carried out using optical microscopy and scanning electron microscopy (SEM), while chemical composition was determined by FTIR spectroscopy. The results revealed that the microplastic particles ranged in size from a few to several tens of micrometers and exhibited diverse morphologies. Component identification confirmed the presence of potentially irritating, allergenic, and asthma-inducing substances such as acrylates. These findings highlight the need for further investigation into inhalation exposure among beauty salon workers, as well as the necessity of emission control strategies for microplastics in such environments. Full Text: PDF References M.O. Rodrigues, N. Abrantesb, F.J.M. Gonçalvesa, H. Nogueira, J.C. Marquesd, A.M.M. Gonçalvesa, "Impacts of plastic products used in daily life on the environment and human health: What is known?", Environm. Toxicology Pharmacology 72, 103239 (2019), CrossRef R.C. Thompson, C.J. Moore, F.S. vom Saal, S.H. Swan, "Plastics, the environment and human health: current consensus and future trends", Philosophical Transactions of the Royal Society B: Biological Sciences, 364, 1526 (2009), CrossRef J.P.G.L. Frias, R. Nash, "Microplastics: Finding a consensus on the definition", Marine Pollution Bulletin, 138 (2019), CrossRef Defining Primary and Secondary Microplastics: "Defining Primary and Secondary Microplastics: A Connotation Analysis", A Connotation Analysis, J. Song, C. Wang, G. Li, ACS EST Water , 4, 6 (2024), CrossRef Y. Li, L. Tao, Q. Wang, F. Wang, G. Li, M. Song, "Potential Health Impact of Microplastics: A Review of Environmental Distribution, Human Exposure, and Toxic Effects", Environment and Health 1, 4 (2023). CrossRef K. Ziani, C.-B. Ioniță-Mîndrican, M. Mititelu, S.M. Neacșu, C. Negrei, E. Moroșan, D. Drăgănescu, O.-T. Preda, "Microplastics: A Real Global Threat for Environment and Food Safety: A State of the Art Review", Nutrients. 15, 3 (2023), CrossRef M. Liro, A. Zielonka, "Towards a geography of plastic fragmentation", Microplastics and Nanoplastics, 5, 1 (2025), CrossRef E.-Y. Chen, K.-T. Lin, C.-C. Jung, C.-L. Chang, C.-Y. Chen, "Characteristics and influencing factors of airborne microplastics in nail salons", Science of The Total Environment 806, 151472 (2022). CrossRef Workplace atmospheres – Size fraction definitions for measurement of airborne particles DirectLink